1985
DOI: 10.1104/pp.78.2.241
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Invertases

Abstract: Wheat coleoptiles have two distinct invertases, a soluble and a cell wall-bound form as indicated by results from cytochemical and biochemical studies. These enzyme activities differ in their pH optima, chromatographic behavior on diethyaminoethyl cellulose, kinetic properties, thermal stability, and response to light treatment. The soluble invertase was purified to near homogeneity by diethylaminoethyl-cellulose, concanavalin-A Sepharose, and Sephacryl S-300 chromatography. MATERIALS AND METHODS Buffer Soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(38 citation statements)
references
References 20 publications
2
36
0
Order By: Relevance
“…A strong inhibition of the cell wall invertases from U. dioica (3) and Triticum aestivum (15) was demonstrated for micromolar concentrations of p-chloromercuribenzoyl sulfonate, while millimolar concentrations of DTT (3) were needed to activate the enzyme. The absence of any inhibitory effect of NEM, as previously reported for the T. aestivum enzyme (15), suggests that the sensitive SH-group(s) may be either exposed only at the enzyme's pH optimum (here NEM is not reactive) or during the catalytic cycle. The binding of cell wall invertase to a organo-mercurial derivative of Bio-gel (13) in the absence of substrate argues against the second interpretation, but different SH-groups may be involved.…”
Section: Cells (4)supporting
confidence: 49%
See 1 more Smart Citation
“…A strong inhibition of the cell wall invertases from U. dioica (3) and Triticum aestivum (15) was demonstrated for micromolar concentrations of p-chloromercuribenzoyl sulfonate, while millimolar concentrations of DTT (3) were needed to activate the enzyme. The absence of any inhibitory effect of NEM, as previously reported for the T. aestivum enzyme (15), suggests that the sensitive SH-group(s) may be either exposed only at the enzyme's pH optimum (here NEM is not reactive) or during the catalytic cycle. The binding of cell wall invertase to a organo-mercurial derivative of Bio-gel (13) in the absence of substrate argues against the second interpretation, but different SH-groups may be involved.…”
Section: Cells (4)supporting
confidence: 49%
“…Recently, a number of higher plant cell wall invertases (EC 3.2.1.26) have been purified and characterized (3,5,6,9,13,15,17,(22)(23)(24)37). The enzyme, which has an acidic pH optimum and is positively charged (pI 9-10) at the pH of the cell wall, hydrolyzes sucrose in the apoplast in rapidly growing tissues and has been proposed to be involved in establishing metabolic sinks (25,33, and literature cited therein).…”
mentioning
confidence: 99%
“…The neutral invertase from muskmelon mesocarp has a higher Km value (10 mM) for sucrose than that of the acid invertase (2.2 mM) as in the case for other plant tissues (7,13) and cultured cells (14). Inhibition of activity by Hg2" ions seems to be common to most plant invertases (6,8,13) and the partial inhibition of the neutral invertase by Cu2> and Zn 2 ions resembles the effects of these ions on the alkaline invertase from sugar beet (13).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the wallbound invertases can be released by treatment with a highmolarity solution of NaCl (6,8,11,12,14) and with chelating agents such as EDTA (11,14). Schaffer et al (18) found considerable invertase activity in cell walls of muskmelon mesocarp tissue which was not an artifact of extraction.…”
mentioning
confidence: 99%
“…Plant invertases are usually categorized according to their pH and their spatial location. Acid invertases are generally considered to be localized within the vacuole and/or the cell wall (Pressey, 1966;Krishnan et al, 1985;Salzer and Hager, 1993). Alkaline invertase is thought to be a cytosolic enzyme (Ricardo and ap Rees, 1970), although no direct evidence is available as yet.…”
mentioning
confidence: 99%